First person - Takashi Owaki (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Takashi Owaki is first author on ' Involvement of the liver-gut peripheral neural axis in nonalcoholic fatty liver disease pathologies via hepatic HTR2A', published in DMM. Takashi is an MD and PhD student in the lab of Kenya Kamimura and Professor Shuji Terai at Niigata University, Niigata, Japan, investigating the effect of inter-organ communication on liver diseases via the autonomic nervous system.